The Effect Of Internship Quality Toward Self-Perceived Employability Through The Mediation of Career-Entry Worries For Final Year Student at Universitas Indonesia - Sakapurnama, Eko; Hasan, Siti Amalia (The Asian Journal of Technology Management (AJTM), 2023)
Competition in the world of work is getting tougher over time which triggers a sense of worry and lack of confidence to enter the world of work for young people who do not have work experience, particularly fresh graduates. It is theorized in this paper that, by participating in internship, students can increase their self-perceived employability, thereby reducing their career-entry worries. Specifically, the purpose of this study was to analyze the effect of internship quality on self-perceived employability through the mediation of reduced career-entry worries for final year students at Universitas Indonesia. This study administered online surveys (with 209 respondents) and in-depth interviews (with 3 source persons). The results show that internship quality has a positive influence on self-perceived employability and reduced career-entry worries. Further, self-perceived employability also positively affects reduced career-entry worries and reduced career-entry worries mediate the effect between internship quality and self -perceived employability. This study recommends that universities in Indonesia can implement a compulsory internship program for its students equally.